2018
DOI: 10.1038/emm.2017.164
|View full text |Cite
|
Sign up to set email alerts
|

In vitro modeling of hepatocellular carcinoma molecular subtypes for anti-cancer drug assessment

Abstract: Tractable experimental model that accounts for inter-tumor molecular heterogeneity is a key element of anti-cancer drug development. Hepatocellular carcinoma is known to exhibit highly heterogeneous molecular aberrations across the tumors, including somatic genetic and epigenetic alterations. Previous studies showed that molecular tumor subtypes determined by transcriptome, as a comprehensive functional readout, are reproducibly observed across global patient populations irrespective of geographic and etiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 32 publications
(39 reference statements)
1
46
0
Order By: Relevance
“…Based in the fact that stemness feature is increasing in spheroid or 3D culture, particularly in cells used in this study [29,30], we observed that the number and the size of spheroids decreased in the presence of GDF11 at 72 h of repeated treatment (50 ng/ml, every 24 h) in both HCC cell lines. We found similar effects in HepG2 ( Figure 7A), a human hepatoma cell line capable to form spheroids as well [30], and in SNU-182, another human HCC cell line from a high aggressive tumor.…”
Section: Hcc Accounts For 90% Of Primary Liver Cancer With Increasinmentioning
confidence: 79%
See 1 more Smart Citation
“…Based in the fact that stemness feature is increasing in spheroid or 3D culture, particularly in cells used in this study [29,30], we observed that the number and the size of spheroids decreased in the presence of GDF11 at 72 h of repeated treatment (50 ng/ml, every 24 h) in both HCC cell lines. We found similar effects in HepG2 ( Figure 7A), a human hepatoma cell line capable to form spheroids as well [30], and in SNU-182, another human HCC cell line from a high aggressive tumor.…”
Section: Hcc Accounts For 90% Of Primary Liver Cancer With Increasinmentioning
confidence: 79%
“…It was reported that Huh7 cell line expresses some of the key stemness markers, such as Nanog, Oct4 or Sox2. It has been also reported that increased expression of these genes in Huh7 cells is related to the increment of stemness [28,29], particularly when cells are forming spheroids [30]. The first evidence that Huh7 and Hep3B cells respond to GDF11 was the activation of one of the canonical signal transducers, specifically the phosphorylation of Smad3 [11,20], which was strongly detected after 5 min of GDF11 treatment in the case of Huh7 and, at 30 min in Hep3B cells, and remained activated along 60 min ( Figure 1A).…”
Section: Hcc Accounts For 90% Of Primary Liver Cancer With Increasinmentioning
confidence: 96%
“…HCC is one of the deadliest cancers, partly due to a lack of effective treatments. The failure of molecular targeted therapies is likely due to the intra‐ and inter‐tumor molecular heterogeneity of HCC tumors resulting from different types of molecular aberrations, ultimately leading to patient‐specific dysregulation of molecular pathways …”
Section: Discussionmentioning
confidence: 99%
“…Cancer cell lines are valuable in vitro models for analyzing genetic heterogeneity within tumors and for screening pharmacologic agents for anticancer assessment . Recently, on the basis of transcriptome meta‐analysis of 603 clinical HCC tissues, HCC cell lines have been classified into subtypes .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that global transcriptome profiles classify human HCC cell lines into two groups according to AFP expression levels [ 17 ]. Furthermore, the two subgroups mimic transcriptional dysregulation observed in either or the AFP-positive (S2) or negative (S1) HCC subtypes [ 17 ]. Of note, these subgroups of HCC cell lines show a distinct response to molecular targeted agents.…”
Section: Molecular Subtype-guided Preclinical Drug Discoverymentioning
confidence: 99%